2018
DOI: 10.1002/glia.23534
|View full text |Cite
|
Sign up to set email alerts
|

PPARβ/δ‐agonist GW0742 ameliorates dysfunction in fatty acid oxidation in PSEN1ΔE9 astrocytes

Abstract: Astrocytes are the gatekeepers of neuronal energy supply. In neurodegenerative diseases, bioenergetics demand increases and becomes reliant upon fatty acid oxidation as a source of energy. Defective fatty acid oxidation and mitochondrial dysfunctions correlate with hippocampal neurodegeneration and memory deficits in Alzheimer's disease (AD), but it is unclear whether energy metabolism can be targeted to prevent or treat the disease. Here we show for the first time an impairment in fatty acid oxidation in huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 59 publications
2
26
0
Order By: Relevance
“…In our study, the infliximab group showed a high immunostaining of PPARγ and low immunostaining of TNF‐α. Exposure to M2 (anti‐inflammatory microglia) supernatant induced PPARγ expression and activated neural stem/progenitor cells, increasing and reducing neural inflammation and GFAP + astrocyte cells . And similar to our study, in each the GFAP was increased in saline group, in experimental models of temporomandibular joint inflammation‐induced hypernociception, GFAP overexpression was directly associated with morphological alterations of the trigeminal nerve …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In our study, the infliximab group showed a high immunostaining of PPARγ and low immunostaining of TNF‐α. Exposure to M2 (anti‐inflammatory microglia) supernatant induced PPARγ expression and activated neural stem/progenitor cells, increasing and reducing neural inflammation and GFAP + astrocyte cells . And similar to our study, in each the GFAP was increased in saline group, in experimental models of temporomandibular joint inflammation‐induced hypernociception, GFAP overexpression was directly associated with morphological alterations of the trigeminal nerve …”
Section: Discussionsupporting
confidence: 87%
“…The PPAR‐γ agonist pioglitazone effectively reduced symptoms of depression induced by sciatic nerve ligation causing neuropathic pain in chronic constriction injury, and PPAR‐γ activators have been documented to attenuate spinal nerve transection and partial sciatic nerve ligation‐induced neuropathic pain . Moreover, PPARβ/δ/β agonists ameliorate dysfunction in fatty acid oxidation and glial fibrillary acidic protein (GFAP)‐immunoreactivity in PSEN1Δ/ΒE9 astrocytes, suggesting that transient nNOS trigeminal overexpression (spiked after one day of ODI induction) can be suppressed by PPAR.…”
Section: Discussionmentioning
confidence: 99%
“…Astrocytes generated from patients carrying both FAD-linked PSEN1 M146L and SAD-linked APOE4 mutations exhibited reduced morphological complexity and altered localization of marker proteins, indicating similar effects of FAD and SAD mutations [126]. PSEN1 ΔE9 astrocytes showed elevated release and reduced uptake of Aβ 42 , altered Ca 2+ homeostasis, increased reactive oxygen species production, altered cytokine release and impaired fatty acid oxidation [128,129]. iPSC-derived astrocytes have also been shown to promote the survival, maturation and function of cocultured human neurons, effects that can be impaired by PSEN1 ΔE9 and APOE4 mutations [128,130,131].…”
Section: Astrocytesmentioning
confidence: 99%
“…Other FAO modulators include the CPT1a inhibitor oxfenicine and PPARs agonists/antagonists. Accordingly, the impairment in FAO observed in astrocytes derived from induced pluripotent stem cells isolated from Alzheimer's disease patients is corrected by PPARβ/δ agonists (Konttinen et al, 2019). The specificity of the metabolic modifiers ranolazine (Ranexa) and trimetazidine, initially described as partial FAO inhibitors that target the HAD (or 3-KAT) activity of the trifunctional protein HADHA, has been recently questioned (Ma et al, 2020).…”
Section: Fa Oxidation (Fao) In Astrocytes: the "Missing Link"mentioning
confidence: 99%